1959
DOI: 10.1001/archpedi.1959.02070010593009
|View full text |Cite
|
Sign up to set email alerts
|

Kernicterus in Rats with an Inherited Deficiency of Glucuronyl Transferase

Abstract: This paper describes the occurrence of kernicterus and factors which influence its development in the strain of rats * first studied by Gunn.22,23 The disease of humans designated in 1903 by Schmorl 39 as kernicterus has, in our opinion, not been observed or induced in its entirety in animals. Various workers, however, have demonstrated the toxicity of indirect bilirubin. [12][13][14][15]24,26,[44][45][46]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
1
1

Year Published

1961
1961
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 26 publications
5
64
1
1
Order By: Relevance
“…few days after birth [11]. The hyperbilirubinemia is a Recently, it was reported that the adult homozygous ODELL (jj) rat, in comparison with the non-jaundiced heterozygous (jj) animal, is unable to form concentrated urine and develops hyperosmolality of the extracellular fluids when thirsted [18].…”
Section: Introductionmentioning
confidence: 99%
“…few days after birth [11]. The hyperbilirubinemia is a Recently, it was reported that the adult homozygous ODELL (jj) rat, in comparison with the non-jaundiced heterozygous (jj) animal, is unable to form concentrated urine and develops hyperosmolality of the extracellular fluids when thirsted [18].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The threshold at which B F produces changes in cellular function culminating in permanent cell injury and cell death has been the subject of considerable debate and study for some time. Recently, Daood and Watchko 4 calculated central nervous system (CNS) B F levels in Gunn rat pups during peak postnatal hyperbilirubinemia (day of life 15 to 19) 5,6 and correlated those levels with the cerebellar weights and neurobehavioral status of the pups. 4 The Gunn rat 7 offers an excellent model to explore this relationship in vivo, as it spontaneously develops newborn jaundice and differs from other models that rely on artificially induced hyperbilirubinemia.…”
mentioning
confidence: 99%
“…It is thus likely that any small differences in UB in clinical studies will not be detectable with standard methods, also due to differences and variations in binding capacity and TB levels both in the same infant as well as between infants. In vivo experiments of bilirubin displacement have also shown that this shift of UB into tissue compartments may actually cause a decrease in TB concentrations in plasma (16). With regard to this, it is interesting to note that in the study by Aranda et al (Aranda et al, Plasma unbound bilirubin and ibuprofen in preterms.…”
Section: Discussionmentioning
confidence: 95%
“…These drugs are able to displace bilirubin from its binding sites on albumin, thus increasing the UB concentration and toxicity. This has been demonstrated clinically by increased mortality and kernicterus in newborn infants treated with sulfisoxazole (15) as well as experimentally in vivo in Gunn rats given such treatment (16). Drugs that displace bilirubin from albumin generally have a strong binding to albumin (13).…”
mentioning
confidence: 99%